Modelos de representação cartográfica de dinâmicas espaciais e sua contribuição para o planejamento territorial do município de Mojuí dos Campos/PA - SALIM, Ana Cristina Ferreira (Universidade Federal do Pará, 2018)
This paper deals with models of cartographic representation of spatial dynamics, based on methodological techniques presented by Professor of the University of São Paulo (USP), Dr. Marcello Martinelli, in "Dynamic Mapping: Maps in Time and Space." Here is discussed the contribution of these techniques as a tool for construction process planning. In order to further this analysis, we performed an application of these to the newly created municipality of Moju dos Campos, State of Pará This case study was demonstrative character, considered only the dynamic aspect of land use in that territory. Subsidies were used as official secondary data, from public institutions, and data use and land cover, published in 2008, produced under the Modeling Project Amazon (GEOMA Network), which the author was a member. Thus, more than one product to serve as territorial planning of the study area chosen, this work aims to reflect on the potential of cartographic representations of spatial dynamics to the process of planning.